2010
DOI: 10.4314/ajpherd.v15i4.49552
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a 12-week exercise programme on bone mineral density in young South African females

Abstract: A longer lifespan has increased the emphasis on bone health, which is often compromised with age. Studies have shown that exercise yields a positive influence on bone mineral density (BMD), especially when done during the early years of life (second to third decades). A 12-week study was undertaken using dual-energy X-ray absorptiometry (DEXA) to assess changes in BMD (total, lumbar and neck of the femur) in 70 females (mean age 20.1 years) before and after a 12-week intense exercise programme. The exercise pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…According to the results, healthy people were physically more active than those with pathologic bone fractures, and there were usually sports activities in their daily schedule. These results are consistent with Christos et al ,[7] Egbunikei et al ,[8] Langsetmo et al [9] and Winklmayr et al [10]…”
Section: Discussionsupporting
confidence: 92%
“…According to the results, healthy people were physically more active than those with pathologic bone fractures, and there were usually sports activities in their daily schedule. These results are consistent with Christos et al ,[7] Egbunikei et al ,[8] Langsetmo et al [9] and Winklmayr et al [10]…”
Section: Discussionsupporting
confidence: 92%
“…In a study of Egbunike et al [40] to the effect 12-week program of exercise on BMD femoral neck, BMD significantly increased.…”
Section: Discussionmentioning
confidence: 96%
“…In another study investigating the effect of exercising on bone density, body balance, and self-efficacy of women revealed that compared to the control group, bone density in the femur and body balance were significantly enhanced in the intervention group; however, self-efficacy of two groups was not changed (Jessup, Horne, Vishen, & Wheeler, 2003). Egbunike et al (2009) investigated the effect of a 12-week exercise program on BMD of the neck, waist and femur in 70 women aged from 18 to 22 and indicated a significant increase in BMD of the waist, neck, and femur of studied subjects after intervention. Cohen et al (2013) indicated that family-based intervention causes the enhancement of bone density of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The tool used for gathering data was a questionnaire for evaluating demographic information (age, body mass index [BMI], job status, educational level, household income, number of deliveries, consumption of tobacco production, and family history in osteoporosis) and constructs of PRECEDE model. This questionnaire was arranged based on other similar studies (Babatunde et al, 2011;Egbunike et al, 2009;Ghaffari et al, 2012;Jeihooni et al, 2015;Khani Jeihooni et al, 2017;Madureira et al, 2010;Tabasi Nejad et al, 2018). Twenty-five questions were asked about knowledge of osteoporosis and prevention behaviors and each correct answer had a score of 1 and each incorrect or "no idea" answer had a score of 0.…”
Section: • • Sixth and Seventh Sessions: The Role Of Exercisingmentioning
confidence: 99%
See 1 more Smart Citation